ACTIVE TOURISM IN CONTACT WITH NATURE – AN INNOVATIVE PRODUCT FOR SCHOOL TOURISM - Tomik, Rajmund (Acta Scientiarum Polonorum. Oeconomia, 2010)
Active tourism is a form of tourism whereby its participants combine recreation, sport, development of physical fitness, visiting places, and different forms of physical activity. Nature-bound school tours allow continuing the education of children and youth in natural settings. A survey was conducted to estimate the offer of nature-bound active tourism provided by Polish schools. Two hundred and ninety-two physical education teachers throughout Poland entered the study. The respondents of the diagnostic survey confirmed that the majority of schools organized tours or other tourist events. However, the frequency of these events was inadequate compared to the needs of contemporary children and youth. Thus, it seems necessary to create a range of innovative products for active tourism during school years, which would broaden this type of activity among the largest possible fraction of schoolchildren population.